Human-centered design maturity assessment for CGIAR - Muller, Anna (2025)
The Digital Transformation Accelerator’s mission depends on people-centered digital transformation. Enabling responsible AI and digital transformation requires solutions grounded in the needs, contexts, and realities of the people affected by them. Human-Centered Design has become an approach that is increasingly promoted to address this challenge in digital transformation. But design is more than methods. Its impact depends on how consistently insights inform decisions, priorities, and solution design, not just on using tools or workshops. The organizational maturity determines the impact of human-centered design. Culture, leadership, incentives, budgeting, strategy, and collaboration shape whether design can be practiced effectively and at scale. Maturity helps us move from intent to capability. This presentation outlines an assessment of design maturity in CGIAR. Understanding our current maturity allows us to identify constraints, focus investments, and strengthen HCD as an organizational capability — not an individual effort.